Teaching Legal Ethics Online: Pervasive or Evasive? - Archie Zariski (Legal Education Review)
The aim of this article is to encourage law teachers to produce interactive teaching/learning materials in law and to share the lessons that they learn from their work to enrich what we know about the development of, and student learning with, multimedia teaching/learning products. In this article I describe the process of the creation of an interactive CD-ROM designed to teach law students and trainee legal practitioners legal ethics and professional responsibility (“LE/PR”). I outline some of the problems that were faced and the lessons that were learned so that other law teachers and multi-media developers might profit from them and more confidently embark on producing interactive teaching/ learning materials that enrich learning in law. In so doing, I hope to be able to contribute to the development of a scholarship of teaching as advocated by Boyer and other educationalists and translate what Laurillard suggests about teaching and learning with multi-media into practice.